2015
DOI: 10.1007/s13193-015-0462-4
|View full text |Cite
|
Sign up to set email alerts
|

Genital Sparing Cystectomy for Female Bladder Cancer and its Functional Outcome; a Seven Years' Experience with 24 Cases

Abstract: The surgical treatment of bladder cancer is the curative treatment especially in early cases. In this study, our aim was to assess the outcome of preservation of internal genital organs in selected females both oncologically and functionally, and to assess the feasibility of technique and its complication. 24 females with clinically and radiologically diagnosed T2 bladder cancer underwent gynecologic-tract sparing cystectomy (GTSC). Age ranged from 45 to 60 years. Patients with diffuse carcinoma-in-situ, those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Salem et al reported the pathological findings of gynecologic organs obtained in female RC (n=250) performed for urothelial carcinoma. 3 Malignancy was identified in 1 uterus and 11 vagina specimens, including invasive urothelial carcinoma, all of which were clearly identified intraoperatively. They concluded that preservation of internal genitalia should be considered in selected cases after careful preoperative assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salem et al reported the pathological findings of gynecologic organs obtained in female RC (n=250) performed for urothelial carcinoma. 3 Malignancy was identified in 1 uterus and 11 vagina specimens, including invasive urothelial carcinoma, all of which were clearly identified intraoperatively. They concluded that preservation of internal genitalia should be considered in selected cases after careful preoperative assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Day time and night urinary continence rates were 95.4% and 90.2%, respectively. 3 Ali-El-Dein et al reported the outcomes of 15 female cases who underwent genitalia sparing open RC with orthotopic neobladder reconstruction. They included patients with clinical stage T2bN0M0 or less disease, unifocal tumors away from the trigone, sexually active young women and without any clinical suspicion of the involvement of internal genitalia by tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potency evaluation only included patients with potent erections preoperatively, and potency rates differed based on NS status with 10% (2/20) potent if no attempts at nerve sparing, 52% (42/81) if unilateral, and 72% (31/43) if bilateral NS [18]. Multiple studies suggest that uterine preservation and sparing the anterior vaginal wall can improve sexual function and is comparable to standard oncologic outcomes for radical cystectomy in well-selected female patients [19,20]. Women with bulky posterior wall tumors and cancer at the bladder base should be excluded from organ-sparing techniques given the higher chance for recurrence.…”
Section: Sexual Functionmentioning
confidence: 99%
“…Cystectomy with preservation of the internal genital organs is feasible in women with early, solitary or T2 bladder cancer with satisfactory functional and oncological outcomes with proper case selection …”
Section: Techniquementioning
confidence: 99%